The Geothermal Resource in the Guanacaste Region (Costa Rica): New Hints From the Geochemistry of Naturally Discharging Fluids - Tassi, Franco; Vaselli, Orlando; Bini, Giulio; Capecchiacci, Francesco; de Moor, J. Maarten; Pecoraino, Giovannella; Venturi, Stefania (Frontiers in Earth Science, 2018)
The Guanacaste Geothermal Province (GGP) encompasses the three major volcanoes of northern Costa Rica, namely from NW to SE: Rincón de la Vieja, Miravalles and Tenorio. The dominant occurrence of (i) SO4-rich acidic fluids at Rincón de la Vieja, (ii) Cl-rich mature fluids at Miravalles and (iii) HCO3--rich and low-temperature fluids at Tenorio was previously interpreted as due to a north-to-south general flow of thermal waters and a magmatic gas upwelling mostly centered at Rincón de la Vieja, whereas Miravalles volcano was regarded as the typical geothermal system. The uniformity in chemical and isotopic (R/Ra and 34S) compositions of the neutral Cl-rich waters suggested to state that all the thermal discharges in the GGP are linked at depth to a single, regional geothermal reservoir. In this scenario, the thermal manifestations related to Tenorio volcano were regarded as a distal and diluted fluid outflow. In this study, a new gas geochemical dataset, including both chemical and isotopic (13C-CO2 and R/Ra) parameters of fluid discharges from the three volcanoes, is presented and discussed. Particular attention was devoted to the Tenorio thermal manifestations, since they were poorly studied in the past because this area has been considered of low geothermal potential. The aim is to provide insights into the magmatic-hydrothermal fluid circulation and, to verify the spatial distribution of the heat fluid source feeding the fluid manifestations. Our results only partially confirm the previously depicted model, because the geochemical and isotopic features (e.g. relatively high concentrations of temperature-dependent gases and high R/Ra values) shown by fluids seeping out from the southern sector of Tenorio volcano are more representative of medium-to-high enthalpy volcanic systems than those typically occurring in distal areas. This implies that the geothermal potential in the south of the GGP is higher than previously thought.